ANALISIS PERBANDINGAN DIFERENSIASI PRODUK DAN CITRA MEREK PADA SEPEDA MOTOR HONDA PCX DAN YAMAHA NMAX DI KEMBANG JANGGUT - Onky Wijaya; Hendra; Akhmadiansyah Akhmadiansyah (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2024)
Nowadays, the technological development at business have led to the emergence of products with various new brands. This increases the level of competition between similar businesses, so that consumers are faced with many forms of choice of product types, and consumers are free to determine the product of their choice. This situation forces consumers to be more picky in choosing products, so companies need to think about the best marketing strategy so that consumers can be satisfied with the products and services provided. And one of the competitions is in the motorcycle segment. This study aims to analyze how the differences in product differentiation and brand image on Honda PCX and Yamaha Nmax motorcycles. This research is quantitative research and the collection technique is purposive sampling using each respondent as many as 100 respondents using Honda PCX and Yamaha PCX the research instrument is a questionnaire that is analyzed using the Mann Whitney different test. Based on the research results obtained, it is known that there are no significant differences in product and brand image between Honda PCX and Yamaha PCX motorcycles on Kembang Janggut.